2006
DOI: 10.1063/1.2172708
|View full text |Cite
|
Sign up to set email alerts
|

Employing ambipolar oligofluorene as the charge-generation layer in time-of-flight mobility measurements of organic thin films

Abstract: Strong absorption of oligofluorenes at wavelengths of a few commonly used nanosecond pulsed lasers, their bipolar transport characteristics, and high mobilities for both holes and electrons make them useful as the general and effective charge-generation material for the time-of-flight mobility measurement of organic materials. In this letter, we demonstrate the use of the terfluorene as the charge-generation material for measuring hole and electron mobilities of various organic materials. Such a scheme has the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(56 citation statements)
references
References 15 publications
0
55
1
Order By: Relevance
“…Calculated μ e ’s of TPBI were ~10 −5 cm 2 /(V∙s), which concurs with those measured by using time of flight in a previous report (fig. S18) ( 49 ). μ e of 2PTPS according to electric field range was on the order of ~10 −4 cm 2 /(V∙s), which is an order higher than that of TPBI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculated μ e ’s of TPBI were ~10 −5 cm 2 /(V∙s), which concurs with those measured by using time of flight in a previous report (fig. S18) ( 49 ). μ e of 2PTPS according to electric field range was on the order of ~10 −4 cm 2 /(V∙s), which is an order higher than that of TPBI.…”
Section: Resultsmentioning
confidence: 99%
“…The higher μ e of our electron-transporting host materials increases electron transport in the EML that includes a hole-transporting host (TCTA) [μ h of TCTA, ~3 × 10 −4 cm 2 /(V∙s)] ( 50 ), thereby leveling the charge-carrier balance and broadening the electron-hole recombination zone in the EML. In contrast, the use of a conventional TCTA/TPBI EML provides relatively poor electron-hole balance because TPBI has lower μ e [~10 −5 cm 2 /(V∙s)] than μ h of TCTA ( 49 ). …”
Section: Resultsmentioning
confidence: 99%
“…The electron mobility of TPBi is determined to be 5.14 × 10 −5 cm 2 V −1 s −1 at 3.6 × 10 5 V cm −1 electric field, which is coincident with the values reported previously. 52,53 At this electric field intensity, the electron mobility of TPE-TPAPBI is as high as 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 18 DPBI were employed as emissive light-emitting layers in nondoped OLED devices to evaluate their EL performances. Both luminogens were further purified through sublimation before Figure 7 illustrates the OLED performance characteristics, and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 1...…”
Section: Electrochemical Propertiesmentioning
confidence: 97%
“…[24] Our group then validated the use of terfluorene E3 as the charge-generation layer (CGL) for measuring hole and electron mobilities of various organic materials. [25] E3 exhibits a reasonably high T g of 104 8C and thus, is capable of forming stable as well as homogeneous amorphous film with vacuum deposition. Furthermore, E3 was found to possess a reasonably high ionization potential (I p ) of~5.9 eV in thin films, and an electron affinity (EA) of 2.7 eV, which indicated that photo-generated carriers of E3 could be easily injected into a wide range of organic materials used in OLEDs.…”
Section: Introductionmentioning
confidence: 99%